Myeloid cell dynamics correlating with clinical outcomes of severe COVID-19 in Japan - Takano, Tomohiro; Matsumura, Takayuki; Adachi, Yu; Terahara, Kazutaka; Moriyama, Saya; Onodera, Taishi; Nishiyama, Ayae; Kawana-Tachikawa, Ai; Miki, Shoji; Hosoya-Nakayama, Kaori; Nakamura-Hoshi, Midori; Seki, Sayuri; et al. (International immunology, 2021)
Transient expansion of PMN-MDSCs before recovery from severe COVID-19 Abstract Abstract An expanded myeloid cell compartment is a hallmark of severe coronavirus disease 2019 (COVID-19). However, data regarding myeloid cell expansion have been collected in Europe, where the mortality rate by COVID-19 is greater than those in other regions including Japan. Thus, characteristics of COVID-19-induced myeloid cell subsets remain largely unknown in the regions with low mortality rates. Here, we analyzed cellular dynamics of myeloid-derived suppressor cell (MDSC) subsets and examined whether any of them correlate with disease severity and prognosis, using blood samples from Japanese COVID-19 patients. We observed that polymorphonuclear (PMN)-MDSCs, but not other MDSC subsets, transiently expanded in severe cases but not in mild or moderate cases. Contrary to previous studies in Europe, this subset selectively expanded in survivors of severe cases and subsided before discharge, but such transient expansion was not observed in non-survivors in Japanese cohort. Analysis of plasma cytokine/chemokine levels revealed positive correlation of PMN-MDSC frequencies with IL-8 levels, indicating the involvement of IL-8 on recruitment of PMN-MDSCs to peripheral blood following the onset of severe COVID-19. Our data indicate that transient expansion of the PMN-MDSC subset results in improved clinical outcome. Thus, this myeloid cell subset may be a predictor of prognosis in cases of severe COVID-19 in Japan. Graphical Abstract Graphical Abstract